Biomimetic fibroblast-loaded artificial dermis with "sandwich" structure and designed gradient pore sizes promotes wound healing by favoring granulation tissue formation and wound re-epithelialization. (15th January 2016) - Wang, Yuzhen; Xu, Rui; Luo, Gaoxing; Lei, Qiang; Shu, Qin; Yao, Zhihui; Li, Haisheng; Zhou, Junyi; Tan, Jianglin; Yang, Sisi; Zhan, Rixing; He, Weifeng; et al.
Graphical abstract: Abstract: The structure of dermal scaffolds greatly affects the engineered tissue's functions and the activities of seeded cells. Current strategies of dermal scaffold design tend to yield a homogeneous architecture with a uniform pore size. However, the structures of the human dermis are not homogeneous in terms of either interstitial spaces or architecture at different dermal depths. In the present study, a biomimetic fibroblasts-loaded artificial dermis composed of three-layer scaffolds with different pore sizes was prepared. The three-layer scaffolds, which look similar to a sandwich, mimic the natural structures of the human dermis, which has comparatively larger pores in the outer layers and smaller pores in the middle layer. The fibroblasts-loaded artificial dermis were shown to favor wound healing by promoting granulation tissue formation and wound re-epithelialization, as determined by a histological study and Western blotting. Our data indicated that the biomimetic fibroblasts-loaded artificial dermis with "Sandwich" structure and designed gradient pore sizes may hold promise as tissue-engineered dermis. Statement of Significance: Pore size effect on wound healing had been extensively studied. However, it is still not well understood whether dermal scaffolds with a uniform pore size are better than that with varied pore sizes, which are similar to human dermis as determined by our previous work. In our study, we demonstrated that the "sandwich" collagen scaffolds mimicking the natural structures of the human dermis significantly promoted wound healing compared with the "Homogeneous" scaffolds with a uniform pore size. These results may be helpful in the design of dermal scaffolds.